A tragédia como um estudo do ser em Hölderlin - Souza, Gabriela Nascimento (2021)
The proposed thesis is to provide a study of the movements of unification, partition, totality, and aesthetic recreation in Friedrich Hölderlin's poetic philosophy. Pure and simple being in its most adventurous oneness has been lost, and once judgment has made itself present, returning to the unity proper to intellectual intuition is impossible. At the heart of the original partition, tragedy enters the scene as aesthetic intuition and recreates intellectual intuition, which is why it is understood as a metaphor of intellectual intuition and not as a return to pure being. The movement between the one and the whole that is proper to being will be recreated in the tragic aesthetic operation, in which being, or intellectual intuition, will reappear as a living totality. Tragedy, as a possibility of understanding the movement between whole and part, can be understood as a study of being, since it consists in the reconstruction of the movement of separation and unification of intellectual intuition in aesthetic intuition.